The skin I live in: Pathogenesis of white-nose syndrome of bats. - Marcos Isidoro-Ayza; Jeffrey M Lorch; Bruce S Klein (PLoS Pathogens)
The emergence of white-nose syndrome (WNS) in North America has resulted in mass mortalities of hibernating bats and total extirpation of local populations. The need to mitigate this disease has stirred a significant body of research to understand its pathogenesis. Pseudogymnoascus destructans, the causative agent of WNS, is a psychrophilic (cold-loving) fungus that resides within the class Leotiomycetes, which contains mainly plant pathogens and is unrelated to other consequential pathogens of animals. In this review, we revisit the unique biology of hibernating bats and P. destructans and provide an updated analysis of the stages and mechanisms of WNS progression. The extreme life history of hibernating bats, the psychrophilic nature of P. destructans, and its evolutionary distance from other well-characterized animal-infecting fungi translate into unique host-pathogen interactions, many of them yet to be discovered.